Diseñando (2015)
TeniendoencuentalasrelacionesestablecidasentreelDiseño,eldiseñador,losdiseñado-resyelentornodentrodelcualsedesenvuelven,sehaceénfasisenlaconstruccióndelasdife-renteshabilidadesdecadadiseñador,estableciendolosvínculosentreellasydeestasfrentealabordajedeunproyectodeterminado.LaUniversidaddeBogotáJorgeTadeoLozanocomoejecentraldelnacimientodelpro-yectoDiseñandandocomprendeunenfoquefrentealasdiferenteshabilidadesquesesuponedebenadquirirlosestudiantesdurantesuformaciónacadémica,deestamanerasepartedelasbasespropuestasdesdeelprogramadeDiseñoIndustrialparaexplorar,comprender,interpretaryconstruirprocesosquecontribuyanhaciaelhallazgoycomunicacióndedichashabilidadesqueadquiereelestudiantealolargodelacarrera.DeestamaneraelpresentedocumentopormediodeunanálisisinterpretativosobrelashabilidadesylaimportanciadeéstasfrentealDiseño,proponeunaherramientaquepermitealestudiante(oacualquierdiseñador)explorar,identificar,comunicareintercambiardemaneraindividualycolectivaloquelocomponecomodiseñadorentantohabilidadesserefiere,permi-tiendounaaproximaciónsubjetivaentreeldiseñadoryunproyectodeDiseño,siendolashabili-dadessusherramientasdeabordaje,desarrolloycomunicación.Conformandoasí,equiposdetrabajodondeelaportecolaborativohaciaunmismoproyectobrindelaposibilidaddeenriquecerlosprocesosdeabordaje,asícomolaadherenciadenuevossaberesdentrodeladisciplina.